Acoustofluidic semen analysis for veterinary male bovine infertility assessment. (3rd February 2023) - Castro, Jasmine O.; Abdul Halim, Melati S.; Ambattu, Lizebona A.; Rezk, Amgad R.; Prabhakar, Ranganathan; Nosrati, Reza; Yeo, Leslie Y.
Abstract: Abstract : We demonstrate through the use of a unique acoustically driven microfluidic extensional rheometry platform (ADMiER) that a single measurement – i.e. the time required for a liquid bridge filament comprising a microlitre semen sample to thin and break up under elastocapillary stresses – constitutes an appropriate proxy for quantifying the motile sperm concentration of the sample in place of computer-assisted sperm analysis (CASA) and haemocytometer measurements used in conventional semen assessment – without the need to separately resolve for individual dependencies on each sperm parameter. By benchmarking diagnostic test accuracy results of blind random bull semen samples ( n=35 ) against OpenCASA measurements of these parameters, ADMiER is capable of predicting sperm quality to 93.7 % accuracy, 91.4 % sensitivity and 97.5 % specificity, with respect to commonly adopted veterinary industry minimum values for fertility. These results therefore highlight the potential diagnostic capability of the platform as a conceptual first step towards the development of a rapid, low-cost and portable alternative for veterinary male bovine fertility assessment.